2017
DOI: 10.1002/jaba.400
|View full text |Cite
|
Sign up to set email alerts
|

Renewed behavior produced by context change and its implications for treatment maintenance: A review

Abstract: Behavioral treatment gains established in one setting do not always maintain in other settings. The present review examines the relevance of basic and translational research to understanding failures to maintain treatment gains across settings. Specifically, studies of the renewal effect examine how transitioning away from a treatment setting could evoke a return of undesirable behavior, rather than newly trained appropriate behavior. Studies of renewal typically arrange three phases, with a response trained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
135
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(142 citation statements)
references
References 143 publications
4
135
0
3
Order By: Relevance
“…Mace et al proposed training appropriate behaviors initially in an alternative context with no reinforcement history for problem behavior. We also incorporated stimulus generalization strategies based on Stokes and Baer (1977) to reduce the likelihood that problem behavior would recur when FCT was implemented in the treatment context (see also Podlesnik et al, 2017a for a related discussion). We also incorporated stimulus generalization strategies based on Stokes and Baer (1977) to reduce the likelihood that problem behavior would recur when FCT was implemented in the treatment context (see also Podlesnik et al, 2017a for a related discussion).…”
Section: Resultsmentioning
confidence: 99%
“…Mace et al proposed training appropriate behaviors initially in an alternative context with no reinforcement history for problem behavior. We also incorporated stimulus generalization strategies based on Stokes and Baer (1977) to reduce the likelihood that problem behavior would recur when FCT was implemented in the treatment context (see also Podlesnik et al, 2017a for a related discussion). We also incorporated stimulus generalization strategies based on Stokes and Baer (1977) to reduce the likelihood that problem behavior would recur when FCT was implemented in the treatment context (see also Podlesnik et al, 2017a for a related discussion).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that we made manipulations similar to those used in studies evaluating extinction cues to decrease operant renewal, or the relapse of previously eliminated responding following a change in context (Podlesnik, Kelley, Jimenez-Gomez, & Bouton, 2017). For example, Nieto, Uengoer, and Bernal-Gamboa (2017) found that the presence of a cue (i.e., tone) from a phase of extinction for lever pressing decreased relapse during a subsequent renewal test.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction between resurgence and renewal has been investigated across species and renewal procedures (Kincaid, Lattal, & Spence, 2015;Liggett, Nastri, & Podlesnik, 2018;Podlesnik, Kelley, Jimenez-Gomez, & Bouton, 2017;Podlesnik et al, 2019;Sweeney & Shahan, 2015;Trask & Bouton, 2016). For example, to investigate superresurgence during ABA renewal, a particular stimulus (stimulus A) might be present during the reinforcement of the target response, a distinct stimulus (stimulus B) might be present during the reinforcement of the alternative response, and stimulus A might be present during extinction.…”
Section: Resultsmentioning
confidence: 99%